POLATJON KAYYUMIY IN MEMORIES OF CONTEMPORARIES (Scientific journal of the Fergana State University, 2023)
This article is aimed at elucidating and commenting on the thoughts and memories expressed by contemporaries, followers, and disciples of Polatjon Qayyumi about his exemplary life, scientific activity and pedagogical skills. Autobiographical, psychological, system-structural, comparative-typological methods were used in the research. As a result, the generalization and completion of opinions about the scientist was achieved. The life and scientific activity of a scientist is extensive and is the basis for many studies.